2021
DOI: 10.1002/chem.202005440
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Emissive Properties by Intramolecular Hydrogen Bonds: Alkyl and Aryl meso‐Substituted Porphycenes

Abstract: Porphycene, a porphyrin isomer, is an efficient fluorophore. However, four‐fold meso substitution with alkyl groups decreases the fluorescence quantum yield by orders of magnitude. For aryl substituents, this effect is small. To explain this difference, we have synthesized and studied a mixed aryl‐alkyl‐substituted compound, 9,20‐diphenyl‐10,19‐dimethylporphycene, as well as the 9,20‐diphenyl and 9,20‐dimethyl derivatives. Analysis of the structural, spectroscopic, and photophysical data of the six porphycenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Among a wide range of π-conjugated molecular receptors such as, e.g., truxenes, porphycenes, hemiporphycenes, , and corrphycenes, calix[4]­arenes are mostly bowl-shaped macrocycles possessing a 3D cavity which is able to accommodate guest molecules inside. Calixarene molecules are based on phenyl rings connected by metyhlene bridges, and they may be successfully modified on their upper or/and lower rims as well as on the benzene rings. Calixarenes possess a variety of properties, including catalytic, ions transport, luminescence, and adsorption, and they can also act as carriers for drugs and other biologically active substances.…”
Section: Introductionmentioning
confidence: 99%
“…Among a wide range of π-conjugated molecular receptors such as, e.g., truxenes, porphycenes, hemiporphycenes, , and corrphycenes, calix[4]­arenes are mostly bowl-shaped macrocycles possessing a 3D cavity which is able to accommodate guest molecules inside. Calixarene molecules are based on phenyl rings connected by metyhlene bridges, and they may be successfully modified on their upper or/and lower rims as well as on the benzene rings. Calixarenes possess a variety of properties, including catalytic, ions transport, luminescence, and adsorption, and they can also act as carriers for drugs and other biologically active substances.…”
Section: Introductionmentioning
confidence: 99%
“…with N…N distance. [48][49][50][51][52] It has also been shown that a properly selected substitution changes the geometry of the porphyrin cavity, bringing its dimensions closer to that of porphycene. As a result of the change in the cavity geometry, an acceleration of hydrogen transfer by orders of magnitude was observed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies have revealed correlations between electronic properties such as fluorescence quantum yield or tautomerisation rate and the hydrogen bond parameters of porphycenes, e.g., the N…N distance. [48][49][50][51][52] It has also been shown that properly selected substituents can alter the geometry of the porphyrin cavity, bringing its dimensions closer to those of porphycene. As a result of a change in cavity geometry, the hydrogen transfer rate was observed to increase by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%